VD_FINDINFO HC / 2015 / 384 vom 26. März 2015 - VD Tribunal cantonal (2015)
PREUVE À FUTUR, FRAIS JUDICIAIRES, DÉPENS, RETRAITVOIE DE DROIT, DROIT D'ÊTRE ENTENDU | 158 al. 1 CPC (CH), 241 al. 2 CPC (CH), 241 al. 3 CPC (CH), 242 CPC (CH), 319 let. b ch. 1 CPC (CH), 321 al. 1 CPC (CH), 53 al. 1 CPC (CH)